Non Muslim acceptance of halal product in Malaysia - Saleh, Hasan; Rajandran, Thurga (Human Resource Management Academic Research Society, 2024)
This study explores understanding of halal among non Muslim consumers in Malaysia, highlighting factors influencing their purchase intentions. Findings indicate halal awareness, certification, marketing, and knowledge significantly impact non-Muslim consumers' willingness to buy halal products. Increased halal awareness enhances trust in product safety and quality, while effective marketing strategies improve perceptions and broaden appeal. The study identifies a growing acceptance of halal products among non-Muslims, driven by health consciousness and ethical considerations. Additionally, halal certification is recognized as a vital trust signal, assuring compliance with high standards. Educational initiatives are essential for addressing misconceptions and fostering a deeper understanding of halal principles. Ultimately, this study underscores importance of halal in promoting cultural diversity and inclusivity within Malaysian society, positioning it as a valuable concept transcends religious boundaries.